2018
DOI: 10.1101/337337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An expanded toolkit for gene tagging based on MiMIC and scarless CRISPR tagging in Drosophila

Abstract: 30We generated new genetic tools to efficiently tag genes in 31 Drosophila. Double Header (DH) utilizes intronic MiMIC/CRIMIC insertions 32 to generate artificial exons for GFP mediated protein trapping or T2A-GAL4 33 gene trapping in vivo based on CRE recombinase to avoid embryo 34 injections. DH significantly increases integration efficiency compared to 35 previous strategies and faithfully reports the expression pattern of genes 36 and proteins. The second technique targets genes lacking coding introns 37 u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Canton‐S was used as the wild‐type control strain. The genotypes of other Drosophila lines used were as follows: amx ΔCDS,ywing2+ , here called amx N to indicate that it is a null allele (Li‐Kroeger et al, ); Df(1)BSC663 (X:9,217,347…9,284,575), in which amx and nearby genes are uncovered by a molecularly defined deletion generated by FLP/FRT‐mediated recombination (Parks et al, ); pecanex 3 ( pcx 3 ), which has a loss‐of‐function pcx allele (Mohler & Carroll, ; Mohler, ); Protein disulfide isomerase ( Pdi )‐ GFP (a protein‐trap Pdi line) (Kelso et al, ); and a line carrying an approximately 3.3‐kbp genomic rescue construct containing wild‐type amx inserted onto a second chromosome phiC31 docking site (VK37), referred to as amx[+] (Jakobsdottir et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Canton‐S was used as the wild‐type control strain. The genotypes of other Drosophila lines used were as follows: amx ΔCDS,ywing2+ , here called amx N to indicate that it is a null allele (Li‐Kroeger et al, ); Df(1)BSC663 (X:9,217,347…9,284,575), in which amx and nearby genes are uncovered by a molecularly defined deletion generated by FLP/FRT‐mediated recombination (Parks et al, ); pecanex 3 ( pcx 3 ), which has a loss‐of‐function pcx allele (Mohler & Carroll, ; Mohler, ); Protein disulfide isomerase ( Pdi )‐ GFP (a protein‐trap Pdi line) (Kelso et al, ); and a line carrying an approximately 3.3‐kbp genomic rescue construct containing wild‐type amx inserted onto a second chromosome phiC31 docking site (VK37), referred to as amx[+] (Jakobsdottir et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The amx N , a null mutant of amx , used in this study was reported before (Li‐Kroeger et al, ). In brief, we designed two guide RNAs (gRNAs) that targets 5ʹ and 3ʹ of the amx coding sequence (CDS) and deleted the amx CDS by replacing it with a yellow wing2+ marker using CRISPR‐mediated homology‐directed repair.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate attP-SA-sfGFP-SD-attP, a scaffold vector that we named pScaffold was produced by integrating annealed oligonucleotides with sequences M13For-attPfor-SbfI-AvrII-attPrev-M13rev in pCasper3 backbone in EcoRI-NotI sites. SA-sfGFP-SD was cloned as a threefragment ligation in pScaffold with linker-SA (amplified from pDoubleHeader (Li-Kroeger et al, 2018) with primers SA-for-Sbf and Linker-SA-rev_BamHI), sfGFP (amplified from pUAST-NLS-sfGFP-3XMyc-PEST with primers sfGFP-for_BamHI and sfGFP-rev_KpnI), and Linker-SD (amplified from pDoubleHeader with primers Linker-SD-for_KpnI and Linker-SD-rev_NotI).…”
Section: Generation Of Templates For Ssdna Productionmentioning
confidence: 99%
“…SICs can also be used to generate conditional alleles of targeted genes (Flip-flop and FLPstop (Fisher et al, 2017;Nagarkar-Jaiswal et al, 2017). Finally, strategies have been developed to convert SICs through genetic crosses rather than by injection (Trojan Exons and Double Header;Nagarkar-Jaiswal et al, 2015b;Diao et al, 2015;Li-Kroeger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%